International centre for the advancement of multidisciplinary studies on socio-economic systems - Banerjee, Suchismita; Mitra, Manipushpak (Frontiers in Physics, 2023)
We start by summarising very briefly the various prior attempts (during the last one and half a decade), some of which were made as independent research centers and others as visiting centers with extensive visiting programs for luminaries from various basic sciences (Mathematics, Physics, Biology, Economics, and Sociology) and students from various institutions around the world for such interdisciplinary fusion of ideas and researches. Additionally, we briefly discuss the efforts that our institute has made (without any visible success so far, as in the other attempts elsewhere). We then emphasise the critical need for such an international center to attract stalwarts in the basic disciplinary fields as well as interested students from around the world in order to comprehend the world's global socio-economic dynamics.